Prophylactic Intravenous Vs Topical Lidocaine to Blunt Stress Response During Laryngoscopy - Adnan Iqbal, Hafiz Muhammad Javed, Khaleel Ahmad, Mahnoor Rafique Butt, Marrium Khalid, Muhammad Adeel Ashfaq, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The stress response is a common phenomenon occurred during laryngoscopy. Although this response can be transient and less harmful in healthy individuals, it might be hazardous among the many patients with underline disorders. Aim of the study: The purpose of the study was to compare the two different routes for lidocaine to determine the blunt stress response during laryngoscopy. Study design: A randomized control study was designed. Method: This randomized control study design was performed in the Department of Anesthesia, Critical Care, and Pain Medicine at Aziz Bhatti Shaheed Teaching Hospital, Gujrat. The duration of the study was from February 2021 to Jun 2022. The participant of this study was 70 in number having age between 30-60 years and was divided into two groups via a computer-generated randomization sheet. The first group name, group-A contains 35 patients, single dose of 200mg intravenous lidocaine was given before the laryngoscopy procedure. The second group was group B consisted of 35 patients who had to receive the topical (spray) lidocaine in a single dose of 200mg. Results: Group-A patients who had received the IV, lidocaine had a systolic blood pressure mean ± SD value of 120.03 ± 9.72 with a p-value of 0.021 which indicate the systolic was under control. Diastolic pressure means ± SD value was 75.81 ± 10.46 with a P-value of 0.012 which shows the significant effect of lidocaine to reduce the pressure. Arterial pressure was measured with mean ± SD = 75.34 ± 9.61 value. Group B patients who received the topical lidocaine dose, shows a 140 ± 10.87 mean ± SD value of systolic blood pressure and diastolic blood pressure mean ± SD value was 85.42 ± 11.01 recorded. Arterial pressure with mean ± SD = 98.34± 9.13 value and significant p-value shows the higher arterial pressure. The use of topical lidocaine was not effectively controlling heart rate as indicated by mean ± SD = 99.87±10.14. Conclusion: Overall, the study suggests that prophylactic intravenous given laryngoscopy will provide a significantly positive response to handle the blunt stress response in a better way as compared to topical use of lidocaine. Keywords: laryngoscopy, Intravenous lidocaine, Topical lidocaine, Stress response